Speech and language therapy for management of chronic cough - Slinger, Claire (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To evaluate the effectiveness of speech and language therapy for treatment of patients with unexplained chronic cough.